Pengaruh Toleransi Ambiguitas dan Keadilan Organisasi terhadap Komitmen Perubahan Organisasi (Studi Restrukturisasi Organisasi pada Pemerintah Provinsi Papua) - Manansang, Rivo; Zain, Djumilah; T, Armanu; Rahayu, Mintarti (Universitas Brawijaya, Indonesia, 2011)
This study investigated the effect of ambiguity tolerance and organizational of justice toward the organizational change commitment mediated by confidence of change's recipient and the employee's Cynical Attitude. This research was applied in the environment of Papua Provincial Government, in implementing organizational change strategies through restrukturisai, to achieve successful organizational change objectives. The sources of data in this study are primary and secondary data. The population of this study are civil servants who occupy the structural position of echelon IV and III, which found as many as 184 people as the research sample. The analytical method used is Structural Equation Modeling (SEM), The results showed that tolerance of ambiguity and organizational justice simultaneously through conviction of employees to accept change and cynicism will affect employees' commitment to organizational change efforts. The confidence of employees' to accept changes in the organization of the employees is high. These degrees will provide a direct impact on low cynicism, and provide an indirect positive impact significantly on the commitment of organizational change.